Correlations Between Erosions and Relative Uplifts From the Central Inversion Zone of the Xihu Depression, East China Sea Basin - Chun-Feng Li; Zuyi Zhou; Heping Ge; Yunxin Mao (Terrestrial, Atmospheric and Oceanic Sciences, 2007)

(untitled)
Late Pliocene - early Pleistocene erosions and relative uplifts in the central inversion zone of the Xihu Depression, East China Sea Basin, are independently determined from reflection seismic data and sonic well-logging data, respectively. Relative uplifts estimated from linear least-square models of 26 sonic wells range from 0.0 to 501.3 m, while absolute erosions estimated on their respective well localities are generally larger, in the range of ~50.0 to 1147.5 m measured directly from seismic data, and ~70.0 to 1700.4 m after decompaction. Although discrepancies exist for several of the wells, a strong positive correlation can be found between erosions and relative uplifts. This good correlation verifies on the one hand that sonic well-logging data can give reasonably good estimates of relative uplifts, and on the other hand that erosions incurred during the basin inversion are strongly tectonically driven. Erosions and relative uplifts appear to be more exponentially than linearly interrelated.